Electronically delocalized Ir enables efficient and stable acidic water splitting. Issue 38 (28th September 2020) - Hu, Hao; Kazim, Farhad M. D.; Ye, Zihao; Xie, Yuhua; Zhang, Quan; Qu, Konggang; Xu, Jingxiang; Cai, Weiwei; Xiao, Shenglin; Yang, Zehui
Abstract : The incorporation of Au to Ir nanoparticles induced electronic delocalization of Ir atoms enables stable and efficient acidic water splitting. Abstract : The industrial electrochemical generation of hydrogen predominantly relies on the polymer electrolyte membrane water electrolyzer (PEMWE). An efficient and stable anodic electrocatalyst is extraordinarily important since the harsh acidic environment is corrosive to the metal-based catalyst, especially at high voltage. In this work, we deposited ultrasmall AuIr alloyed nanoparticles (1.7 nm) on carbon nanotubes (AuIr@CNT) as a bifunctional electrocatalyst for acidic water splitting. Due to the incorporated Au atoms, the neighboring Ir atom is positively charged, resulting in the electronic delocalization of Ir, which is favorable for reducing the energy barrier of the rate-limiting step (O* → OOH*) in the acidic oxygen evolution reaction (OER); thus, the overpotential for 10 mA cm −2 is 257 mV for AuIr@CNT in 0.5 M H2 SO4 electrolyte, which is comparatively lower than that of Ir@CNT (279 mV) and commercial IrO2 (332 mV). Moreover, the mass activity of AuIr@CNT is 70 orders of magnitude higher than that of benchmark IrO2 at a potential of 1.6 V vs. RHE. More importantly, the formed AuIr@CNT electrocatalyst exhibits promising stability compared to commercial IrO2 and Ir@CNT, which is ascribed to the strong electronic interaction between Au and Ir. Subsequently, AuIr@CNT shows superior hydrogen evolution reaction (HER) catalytic activity, which is 6.3 times better than that of the benchmark Pt/C due to the well-constructed AuIr alloy structure at the atomic level triggering a more moderate hydrogen adsorption–desorption strength. The assembled water splitting device requires only 1.51 V to attain an electrocatalytic current density of 10 mA cm −2 for AuIr@CNT, which is lower than that of the Pt/C–IrO2 system (1.6 V); in addition, an excellent stability is also recorded.